ANTIPLATELET DRUGS RESISTANCE IN PATIENTS WITH ISCHEMIC HEART DISEASE AND OBLITERATIVE ATHEROSCLEROSIS OF LOWER LIMB ARTERIES ASSOCIATED WITH DIABETES MELLITUS TYPE 2 - E. V. Gorjacheva; A. E. Udovichenko; V. A. Sulimov; N. V. Lavrishcheva; M. A. Surikova; T. N. Gracheva (Рациональная фармакотерапия в кардиологии)
Aim. To study a rate of resistance to acetylsalicylic acid (ASA) and clopidogrel and clinical outcomes in patients with atherosclerosis and diabetes mellitus type 2 (DM2).Material and methods. 154 patients were involved in the study and split into two groups. 100 patients (47 men, 53 women; aged 66,4±7,8 y.o.) with ischemic heart disease (IHD) (which was presented by angina pectoris, class I-III, or myocardial infarction history) were included into the first group (G1). Other 54 patients (38 men, 16 women; aged 64,1±10,2 y.o.) with IHD associated with obliterative atherosclerosis of lower limb were included into the 2nd group (G2). Platelet aggregation was evaluated by Born's method (inducers of platelet aggregation were arachidonic acid and ADP). Reduction of platelet aggregation ≥20% after arachidonic acid induction was considered as criterion of resistance to ASA. Patients were considered as resistant, partly resistant and sensitive to clopidogrel if platelet aggregation reduced on <10%, 10-29%, and ≥30% respectively.Results. Rate of ASA and clopidogrel resistance in patients with DM2 was significantly higher than these in patients without DM2 (48% vs 16% respectively, р=0,003 in G1; 42% vs 7% respectively, р=0,007 in G2).Conclusion. Resistance to antiplatelet drugs is observed more often in patients with DM2 and can result in increased risk of cardiovascular complications.